Disintegrasi Data Kependudukan antar OPD Layanan Publik Kabupaten Belitung Timur di Tengah Arus Revolusi Industri 4.0 - Risky Ristiandy (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2021)
The industrial revolution 4.0 is a challenge that makes the whole world compete to show capabilities related to the use of the times. In this era of disruption, the need for data and how to perform data in every public service is a list that must be fulfilled by the government in providing trust and effective public services. But the problem of data integration which will become a main thing in the use of integrated data must be faced. Seventy-six years since Indonesia's independence, to this day the data of the entire community has not been integrated and is still stored separately. East Belitung Regency is one of the youngest regencies in Bangka Belitung Islands Province is an example of an area with population data that is not integrated. The disintegration experienced by the government of East Belitung makes public services in East Belitung very conventional and far from digitalization. Problems then arise, such as inaccurate printed data and data synchrony that does not work and the data provided is not in accordance with the bitter that must be accepted by society in the digital era. This research was conducted in order to review the problems that occur related to data integration. that influence and influence the influencing factors in this research, so that later it can conclude the problems and solutions that must be done in order to realize data integration